Nanofrabication and characterization of silver nanoparticles - Tay, Bing Yuan (2019)
Owing to small size effect and large surface area, silver nanoparticle (AgNPs) exhibits special physical properties and is widely used in different applications. One of the significant applications is that AgNPs are coated on the surface of solar cell to increase the light harvesting efficiency of solar cell due to its localized surface plasmon resonance (LSPR) effect. AgNPs could be synthesized through chemical reduction method using silver nitrate as metal precursor, sodium borohydride as reducing agent while 1-dodecanthiol as capping agent. In this study, the effects of the concentration of reducing agent, the concentration of capping agent and reaction temperature on the formation of AgNPs in term of size and shape had been studied and investigated. The synthesized AgNPs were characterized using UV/Vis spectroscopy, Fourier-transform infrared spectroscopy spectrophotometry (FTIR), and X-ray diffraction (XRD), while the surface morphology of AgNPs was studied using scanning electron microscopy (SEM), atomic force microscopy (AFM) and light microscope (LM). The smaller AgNPs with average size of 20-70 nm could be synthesized with an optimum concentration of NaBH4 of 0.36 M (R value = 18), the concentration of DDT of 0.052 M (S value = 0.5) and at 0 oC. The coupling agent, 3-(Trimethoxysilyl)-1-propanethiol (MPTMS) was used as the adhesion promoter to deposit the AgNPs on the surface of solar cell. By coating AgNPs on the surface of solar cell, the greatest improvement of light harvesting efficiency was 108.8 % with 0.136 W.